Biomarkers of immune capacity, infection and inflammation are associated with poor outcome and mortality after stroke - the PREDICT study - Mengel, A. (BMC Neurol, 2019)
BACKGROUND: Almost 40% of stroke patients have a poor outcome at 3 months after the index event. Predictors for stroke outcome in the early acute phase may help to tailor stroke treatment. Infection and inflammation are considered to influence stroke outcome. METHODS: In a prospective multicenter study in Germany and Spain, including 486 patients with acute ischemic stroke, we used multivariable regression analysis to investigate the association of poor outcome with monocytic HLA-DR (mHLA-DR) expression, interleukin 6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor alpha (TNF-alpha) and lipopolysaccharide-binding protein (LBP) as markers for immunodepression, inflammation and infection. Outcome was assessed at 3 months after stroke via a structured telephone interview using the modified Rankin Scale (mRS). Poor outcome was defined as a mRS score of 3 or higher which included death. Furthermore, a time-to-event analysis for death within 3 months was performed. RESULTS: Three-month outcome data was available for 391 patients. Female sex, older age, diabetes mellitus, atrial fibrillation, stroke-associated pneumonia (SAP) and higher National Institute of Health Stroke Scale (NIHSS) score as well as lower mHLA-DR levels, higher IL-6 and LBP-levels at day 1 were associated with poor outcome at 3 months in bivariate analysis. Furthermore, multivariable analysis revealed that lower mHLA-DR expression was associated with poor outcome. Female sex, older age, atrial fibrillation, SAP, higher NIHSS score, lower mHLA-DR expression and higher IL-6 levels were associated with shorter survival time in bivariate analysis. In multivariable analysis, SAP and higher IL-6 levels on day 1 were associated with shorter survival time. CONCLUSIONS: SAP, lower mHLA-DR-expression and higher IL-6 levels on day one are associated with poor outcome and shorter survival time at 3 months after stroke onset. TRIAL REGISTRATION: www.clinicaltrials.gov, NCT01079728, March 3, 2010.